The Influence of Inbound Marketing and Marketing Content On Company Image and Purchasing Decisions at CV Rexindo Multikarya In Samarinda - Norhayati, Norhayati; Hidayati, Tetra; Indriastuti, Herning (Pelopor Publikasi Akademika, 2024)
The purpose of this study is to analyze and prove the effect of inbound marketing and marketing content on company image, to analyze and prove inbound marketing and marketing content on purchasing decisions, to analyze and prove the effect of company image in mediating inbound marketing and marketing content on purchasing decisions. This research was conducted at CV Rexindo Multikarya in Samarinda. The research design uses explanatory research. The type of research is quantitative. The population of this study are respondents who have shopped at CV Rexindo Multikarya in Samarinda. The sample taken for research is 150 respondents with non probability sampling method, namely with purposive sampling technique. Power collection is done by distributing questionnaires to respondents in Samarinda. The data analysis technique used is the SEM method, namely PLS (Partial Least Square) using Smart PLS version 3.0 software. The results showed that inbound marketing and marketing content have a positive and significant effect on company image, inbound marketing and marketing content have a positive and significant effect on purchasing decisions,. In this study also found that inbound marketing and marketing content have a positive and significant effect on purchasing decisions with company image as mediation.